Hypoxia changes the shape of the biomass size spectrum of planktonic communities: a case study in the eastern Mediterranean (Elefsina Bay). (10th November 2020) - Batziakas, Stratos; Frangoulis, Constantin; Tsiola, Anastasia; Nikolioudakis, Nikolaos; Tsagaraki, Tatiana M; Somarakis, Stylianos
Abstract: Hypoxia is a major stressor on biological communities in many oceanic and coastal ecosystems. Various size-dependent processes (e.g. growth and reproduction rates, predator–prey interactions) are adversely affected by hypoxia. We hypothesized that the impacts of hypoxia on planktonic communities would also be reflected in their Normalized Biomass Size Spectra (NBSS) as steeper slopes and lower intercepts. To explore this hypothesis, we studied the planktonic communities (from bacteria to mesozooplankton) of Elefsina, an enclosed bay that exhibits near bottom hypoxia during summer, and Aghios Kosmas, an adjacent coastal site outside the bay. Bottom layer hypoxia formed during the stratification period in Elefsina Bay significantly altered the distribution of planktonic organisms in the water column. Several unicellular and mesozooplanktonic groups avoided the hypoxic layer, in which the biomass of autotrophic picoeukaryotes was markedly higher. Community changes related to hypoxia were clearly reflected in the NBSS. The slope was significantly steeper in the hypoxic layer (−1.330 vs −1.193) and the intercept was lower (−2.222 vs −0.972, hypoxic vs oxic layer). This result can be interpreted as reduced trophic transfer efficiency to the higher trophic levels due to hypoxia.